Aplikasi Metode Hibrid Fuzzy Logic dan Teknik Taguchi untuk Optimasi Multi-Respons pada Proses Bubut Material ST-60 - Wahid, Mohammad Abdul Wahid; Moh. Nur Shodiq1; Pamuji, Dian Ridlo; Kusuma, Dedy Hidayat; Yuliandoko, Herman; Lusi, Nuraini (Software Development, Digital Business Intelligence, and Computer Engineering, 2026)
Surface roughness determines the quality of the lathe process, while the material machining rate indicates productivity. The higher the machining rate of the material, the shorter the cutting time and the higher the productivity. In the metal cutting process, especially the lathe process, it must produce workpieces with quality that meets specifications with a short cutting time. However, this will be difficult to do because the surface roughness characteristics and machining rate of the materials are different. The lower the surface roughness value, the better the quality of the turning process results. Meanwhile, increasing the material processing rate will result in a more productive and faster turning process. To obtain output in the form of optimal surface roughness and material machining rate simultaneously, the selection of turning process parameters must be considered carefully. This research aims to obtain the right turning process parameter settings in order to obtain optimal surface roughness output and material machining rate. The optimization method used is Taguchi-Fuzzy. Based on the results of the experiment, optimization process, and analysis that were conducted, it can be concluded that the combination of process variable levels that simultaneously produce optimum arithmetic surface roughness, average total surface roughness, and material removal rate are as follows: level 1 coolant, using a cold water solvent and air pressure; level 3 spindle speed at 1200 rpm; level 3 feed rate at 0.161 mm/rev; and level 3 cutting depth at 0.5 mm